1996
DOI: 10.1177/089801019601400402
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alternative Therapies among Mexican Americans in the Texas Rio Grande Valley

Abstract: Alternative therapies have gained increasing recognition and usage in North America during the past decade. In a descriptive study with a convenience sample of 213 Mexican Americans, three research questions were asked: (1) What specific kinds of alternative therapies do Mexicans in the Rio Grande Valley use? (2) What percentage of the sample group uses alternative therapies? and (3) Do the users of alternative therapies self-report these visits to their established, conventional, primary health care provider?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 15 publications
6
38
2
Order By: Relevance
“…Even when Diet/Nutrition interventions, which some might consider mainstream rather than alternative, were excluded, the frequency of use of alternative therapies was 42%. These findings extend those of previous studies, which have reported that 11% to 66% of ambulatory patients have used alternative therapies (Anderson et al, 1993;Astin, 1998;Boisset and Fitzcharles, 1994;Coleman et al, 1995;Eisenberg et al, 1993Eisenberg et al, , 1998Elder, 1997;Fleischer et al, 1996;Freeman and Landis, 1997;Gordon et al, 1998;Keegan, 1996;Moser et al, 1996;Rowlands and Powderly, 1991;Spigelblatt et al, 1994). Use of alternative treatments has been reported more commonly in the western parts of the United States, which is consistent with the high use of alternative therapies we observed (Eisenberg et al, 1993;Lerner et al, 1992).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Even when Diet/Nutrition interventions, which some might consider mainstream rather than alternative, were excluded, the frequency of use of alternative therapies was 42%. These findings extend those of previous studies, which have reported that 11% to 66% of ambulatory patients have used alternative therapies (Anderson et al, 1993;Astin, 1998;Boisset and Fitzcharles, 1994;Coleman et al, 1995;Eisenberg et al, 1993Eisenberg et al, , 1998Elder, 1997;Fleischer et al, 1996;Freeman and Landis, 1997;Gordon et al, 1998;Keegan, 1996;Moser et al, 1996;Rowlands and Powderly, 1991;Spigelblatt et al, 1994). Use of alternative treatments has been reported more commonly in the western parts of the United States, which is consistent with the high use of alternative therapies we observed (Eisenberg et al, 1993;Lerner et al, 1992).…”
Section: Discussionsupporting
confidence: 89%
“…A 1998 report of a large, national mail survey found 40% of respondents had used some form of alternative health care in the past year (Astin, 1998). Recent surveys in primary care settings have estimated that 44%-50% of patients have used alternative therapies, but that their physician was informed of these treatments only 34%-53% of the time (Elder et al, 1997;Keegan, 1996). Most studies of alternative medicine in medical settings have been conducted in specialty clinics, among patients with specific diseases, or in unique populations.…”
Section: Introductionmentioning
confidence: 97%
“…Similar practices were also found among Mexican Americans and Dominicans (Allen et al, 2000). Keegan (2000) reported that Mexican Americans used CAM twice as often as Anglo-Americans, including visits to the traditional curanderos (Mexican folk healers) (Keegan, 1996). Maskarinec et al (2000) detected ethnic differences in CAM use among cancer patients.…”
Section: Geographic Variablessupporting
confidence: 51%
“…More expensive therapies such as acupuncture, biofeedback, energy healing, and hypnosis were used by less than 5% of a sample of Florida residents questioned about their lifetime use of CAM (Burg, Hatch, & Neims, 1998). Self-treatment is also common among Chinese immigrants (Ma, 1999), and the use of folk healing is widespread among Mexican-Americans (Keegan, 1996), Hawaiians, and Filipinos (Maskarinec, Shumay, Kakai, & Gotay, 2000). These low-cost CAM alternatives may be more congruent with the patients' culture and beliefs as well as purchasing power, and may explain the statistical prevalence of CAM use in patients from all socio-economic backgrounds.…”
Section: Specific Medical Conditionsmentioning
confidence: 99%
“…As of 2012, 34.9-39.9 percent of people in the LRGV live under the poverty level, in contrast to an average of 17.4 percent throughout Texas (U.S. Census Bureau, 2013). A dual system of human healthcare exists in the LRGV, with contemporary medical services mixed with traditional remedies from folk healers, or "curanderos," and midwives, or "parteras" (Maril, 1989;Thompson, 1993;Burk and others, 1995;Keegan, 1996;Richardson and others, 2012). Workers in the LRGV are often dependent on jobs that can be injurious to their health, pay low wages, and do not provide adequate health insurance.…”
Section: Human Health and Associated Benefits Of Land Conservationmentioning
confidence: 99%